STRENGTH TRAINING WITH ADOLESCENTS IN COMPULSORY SECONDARY EDUCATION: AN EVIDENCE-BASED TEACHING AND METHODOLOGICAL GUIDE - González, Javier; Sáez, Iker; Río, Xabier (Seven Editora, 2025)
This article develops an evidence-based, didactic-methodological guide geared towards the real classroom context for planning, implementing and evaluating strength training in Physical Education during Compulsory Secondary Education. Through a critical synthesis of studies on strength training in young people, the curricular elements are mapped out and the principles of strength training are operationalised in specific teaching decisions. The proposal integrates different methodological approaches, management strategies, organisation and control. Implementation models compatible with the school timetable and a set of resources and instruments for evaluation are described. The results suggest that strength training with adolescents in Physical Education is relevant and safe when it is rigorously planned, supervised and evaluated with valid evidence. The guide offers an operational and transferable framework for departments and teachers, aimed at improving the quality of the teaching-learning process and enhancing the motor skills and health of students. DOI: https://doi.org/10.56238/sevened2025.038-037